Research on computer numerical control machine / Zulkifli Mohamed … [et al.] - Mohamed, Zulkifli; Mohamed, Abdullah; Baharom, Nor Kamarul; Tajudin / Ali, Zamiruddin Omar (Faculty of Mechanical Engineering, Universiti Teknologi MARA, 1999)
In 1947, John Parsons of the Parsons Corporation, began experimenting with the idea of using three-axis curvature data to control machine tool motion for the production of aircraft components. In 1949, Parsons was awarded a U.S Air Force contract to build what was to become the first numerical control machine. In 1951, the project was assumed by the Massachusetts Institute of Technology. In 1952, numerical control arrived when MIT demonstrated that simultaneous three-axis movements were possible using a laboratory-built controller and a Cincinnati 1 Hydrotel vertical spindle. By 1955, after further refinements, numerical control became available to industry. Early NC machines ran off punched cards and tape, with tape becoming the more common medium. Due to the time and effort required to change or edit tape, computers were later introduced as aids in programming. Computer involvement came in two forms: computer aided programming languages and direct numerical control (DNC)…